Lithium battery positive electrode material and manufacturing method thereof

Through copper-titanium nitrogen carbon doping technology, the energy density of lithium nickel manganese oxide materials is improved, the problem of low gram capacitance is solved, and the cost of lithium battery positive electrode materials is reduced.

CN119650610APending Publication Date: 2025-03-18NANYA PLASTICS CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311354849.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-15
Filing Date
2023-10-19
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The current lithium nickel manganate material has a low gram capacitance, resulting in an increase in the cost of lithium batteries.

Method used

Through copper-titanium nitrogen carbon doping technology, the energy density of nickel-manganese lithium manganate material is improved. The specific methods include co-deposition method, filtration process and sintering process, doping copper and titanium, and covering the nitrogen source through the supercritical fluid method.

Benefits of technology

It effectively increases the capacitance of the cathode material of lithium battery, thereby reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004501386880000111
    Figure BDA0004501386880000111
Patent Text Reader

Abstract

The invention provides a lithium battery positive electrode material containing copper, titanium, nitrogen and carbon doped nickel lithium manganate. The invention further provides a manufacturing method of the lithium battery positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a lithium battery positive electrode material and a method for manufacturing the same. Background Art

[0002] At present, lithium nickel manganese oxide materials have a three-dimensional large tunnel structure, good conductivity, and are very suitable for lithium ion diffusion. Therefore, attempts have been made to use them as positive electrode materials for lithium batteries. However, due to their low gram capacity, the cost has increased significantly. Therefore, how to effectively improve the positive electrode materials of lithium batteries, increase their gram capacity, and thus reduce costs is a challenge. Summary of the invention

[0003] The present invention provides a lithium battery positive electrode material and a manufacturing method thereof, which can effectively increase the gram capacity and thus reduce the cost.

[0004] A lithium battery positive electrode material of the present invention comprises copper-titanium-nitrogen-carbon doped lithium nickel manganese oxide.

[0005] In one embodiment of the present invention, the weight ratio of lithium nickel manganese oxide: copper / titanium: nitrogen / carbon in the copper-titanium-nitrogen-carbon doped lithium nickel manganese oxide is between 1:0.4:0.1 and 1:0.1:0.1.

[0006] In one embodiment of the present invention, the average particle size of the copper-titanium-nitrogen-carbon doped lithium nickel manganese oxide is between 0.5 micrometers and 20 micrometers.

[0007] The manufacturing method of a lithium battery positive electrode material of the present invention comprises at least the following steps: performing a coprecipitation method, a filtering process and a sintering process to prepare a precursor of lithium nickel manganese oxide doped with copper and titanium from a copper source, a titanium source and lithium nickel manganese oxide powder; and mixing the precursor of lithium nickel manganese oxide doped with copper and titanium with a carbon source, and coating a nitrogen source with a supercritical fluid method to obtain lithium nickel manganese oxide doped with copper, titanium, nitrogen and carbon.

[0008] In one embodiment of the present invention, the copper source includes copper chloride, copper sulfate, copper sulfite, copper nitrate, copper acetate or a combination thereof.

[0009] In one embodiment of the present invention, the titanium source includes titanium chloride, titanium sulfate, titanium nitrate or a combination thereof.

[0010] In one embodiment of the present invention, the nitrogen source includes dopamine, p-phenylenediamine or a combination thereof.

[0011] In one embodiment of the present invention, the carbon source includes graphene, glucose or a combination thereof.

[0012] In one embodiment of the present invention, the coprecipitation agent used in the above-mentioned coprecipitation method includes water, ethanol, isopropanol, acetone, methyl ethyl ketone, ammonia water, sodium hydroxide, sodium carbonate or a combination thereof, the coprecipitation reaction temperature in the coprecipitation method is between room temperature (25°C) and 100°C, and the coprecipitation reaction time in the coprecipitation method is between 1 minute and 30 minutes.

[0013] In one embodiment of the present invention, the temperature of the sintering process is between 400° C. and 1000° C.

[0014] Based on the above, the present invention uses copper-titanium-nitrogen-carbon doping technology to improve the energy density of lithium nickel manganese oxide materials and solve the problem of low gram capacity. Therefore, the lithium battery positive electrode material of the present invention can effectively increase the gram capacity and thus reduce costs. DETAILED DESCRIPTION

[0015] In the following detailed description, for the purpose of illustration and not limitation, exemplary embodiments that disclose specific details are described to provide a thorough understanding of the various principles of the present invention. However, it will be apparent to one of ordinary skill in the art that, with the benefit of this disclosure, the present invention may be practiced in other embodiments that depart from the specific details disclosed herein. In addition, descriptions of well-known devices, methods, materials, and other specific details may be omitted to avoid obscuring the description of the various principles of the present invention.

[0016] In this article, the range expressed by "a value to another value" is a summary expression method to avoid listing all the values ​​in the range one by one in the specification. Therefore, the description of a specific numerical range covers any value in the numerical range and a smaller numerical range defined by any value in the numerical range, just as the arbitrary value and the smaller numerical range are written in the description text of the specification.

[0017] Unless otherwise specified, the term "between" used in this specification to define a numerical range is intended to cover a range equal to the endpoint value and between the endpoint values. For example, a size range is between a first value and a second value, which means that the size range can cover the first value, the second value and any value between the first value and the second value.

[0018] In this document, non-limiting terms (such as may, could, for example, or other similar terms) mean optional or optional implementation, inclusion, addition, or presence.

[0019] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those commonly understood or generally understood in the technical field to which the present invention belongs. It will also be understood that terms (such as those defined in commonly used dictionaries) should be interpreted as having a meaning consistent with their meaning in the relevant technical context and should not be interpreted in an idealized or overly formal sense unless explicitly defined as such herein.

[0020] In the present embodiment, the positive electrode material of the lithium battery includes lithium nickel manganese oxide doped with copper, titanium, nitrogen and carbon. Accordingly, the present invention uses copper, titanium, nitrogen and carbon doping technology to improve the energy density of the lithium nickel manganese oxide material and solve the problem of low gram capacity. In this way, the positive electrode material of the lithium battery of the present invention can effectively improve the gram capacity and reduce the cost. Here, the weight ratio of lithium nickel manganese oxide: copper / titanium: nitrogen / carbon in the lithium nickel manganese oxide doped with copper, titanium, nitrogen and carbon is between 1:0.4:0.1 and 1:0.1:0.1, and the average particle size of the lithium nickel manganese oxide doped with copper, titanium, nitrogen and carbon is, for example, between 0.5 microns (um) and 20 microns. Here, copper / titanium represents the total proportion of copper and titanium in the lithium nickel manganese oxide doped with copper, titanium, nitrogen and carbon, and nitrogen / carbon represents the total proportion of nitrogen and carbon in the lithium nickel manganese oxide doped with copper, titanium, nitrogen and carbon.

[0021] The manufacturing method of copper-titanium-nitrogen-carbon doped lithium nickel manganese oxide of the present invention may at least include: performing a co-precipitation method, a filtration process and a sintering process to make a copper source, a titanium source and a lithium nickel manganese oxide powder into a precursor of a lithium nickel manganese oxide doped with copper and titanium (the first stage); and mixing the precursor of the lithium nickel manganese oxide doped with copper and titanium with a carbon source, and coating a nitrogen source with a supercritical fluid method to obtain a copper-titanium-nitrogen-carbon doped lithium nickel manganese oxide (the second stage).

[0022] Each step of the method for manufacturing copper-titanium-nitrogen-carbon-doped lithium nickel manganese oxide in one embodiment of the present invention is described below.

[0023] Synthetic lithium nickel manganese oxide powder

[0024] Step 1: Co-precipitate the nickel source, manganese source and polymerization agent to synthesize Ni 0.5 Mn 1.5 O4 precursor, and then wash and dry the obtained powder, and calcine the powder to obtain the initial calcined sample precursor; step 2: add lithium source, dopant and organic medium to the initial calcined sample precursor obtained in step 1 to prepare a stable slurry; step 3: calcine the powder obtained by atomizing and drying the slurry in step 2 to obtain the initial calcined sample LiNi 0.5 Mn 1.5 O4 powder.

[0025] In some embodiments: the nickel source is a nickel salt (such as nickel sulfate, nickel nitrate, nickel acetate), the manganese source is a manganese salt (such as manganese sulfate, lithium manganese nitrate, manganese acetate, manganese chloride), and the lithium source is a lithium salt (such as lithium sulfate, lithium carbonate, lithium chloride); the solvent is (such as distilled water).

[0026] In some embodiments, the specific manufacturing method is as follows.

[0027] First, add water to a laboratory glass container to prepare a reaction solution. Gradually add manganese sulfate to the solution and stir with a three-dimensional mixer, shaker or magnetic stirrer to mix thoroughly.

[0028] Next, 41.83g (0.168 mol) of nickel acetate (Ni(CH3COO)2·4H2O) and 10.38g (0.06 mol) of manganese acetate (Mn(CH3COO)2) were dissolved in 228 ml of ethylenediamine according to the molar ratio of the elements of 1:2.8, and the total concentration of metal ions was 1.0M. 27.5g (0.458 mol) of urea was added according to the molar ratio of urea to metal ions of 2:1, and magnetic stirring was performed for 30 minutes. After magnetic stirring for 2 hours, the mixed solution was transferred to a reaction tank, reacted at 80°C to 170°C for 10 hours, and naturally cooled to room temperature. The resulting precipitate was centrifuged in a centrifuge with a rotation speed of 10000RPM, and the upper clear washing liquid was removed. After that, the precipitate was washed with water and placed in a 120°C oven for drying. After drying, Ni 0.25 Mn 0.75 CO3 precursor.

[0029] Continuing the above, the obtained Ni 0.25 Mn 0.75 The CO3 precursor is first sintered at 400°C to 700°C for 3 hours, and then mixed with LiOH·H2O in a three-dimensional mixing mixer according to Li:(Ni+Mn)=1.05:2 (molar ratio). After mixing evenly, it is calcined at 600°C to 800°C in air for 12 hours, and then heated to 800°C to 1000°C for 10 hours. After natural cooling and grinding, the LiNi 0.5 Mn 1.5 O4 positive electrode material. That is, lithium nickel manganese oxide powder can be obtained. Here, LiNi 0.5 Mn 1.5 All the diffraction peaks of the X-ray diffraction pattern of O4 positive electrode material are consistent with those of standard LiNi 0.5 Mn 1.5 O4 (JCPDS card number 80-2162), indicating that the sample is a cubic spinel structure, Fd-3m space group, each diffraction peak is strong and sharp, indicating that the material is well crystallized and has no Li x Ni 1-x O impurity phase appears.

[0030] Step 4: The pre-fired sample obtained in step 3 is infiltrated and doped, and then calcined and screened to obtain LiNi 0.5-y- x Mn 1.5-y-x Cu x Ti y O4;0<x+y≦0.1,x> 0,y>0 powder, the specific production method is as follows.

[0031] Perform co-precipitation, filtration and sintering processes to make copper source, titanium source and lithium nickel manganese oxide powder into a precursor of lithium nickel manganese oxide doped with copper and titanium

[0032] First, a co-precipitation method is performed to add a copper source and a titanium source to the above-mentioned lithium nickel manganese oxide powder to achieve the purpose of uniform mixing, wherein the copper source includes copper chloride, copper sulfate, copper sulfite, copper nitrate, copper acetate or a combination thereof, and the titanium source includes titanium chloride, titanium sulfate, titanium nitrate or a combination thereof, and the co-precipitation agent used in the co-precipitation method includes water, ethanol, isopropanol, acetone, methyl ethyl ketone, ammonia water, sodium hydroxide, sodium carbonate, oxalic acid or a combination thereof, the co-precipitation reaction temperature in the co-precipitation method is between room temperature (such as 25°C) and 100°C, and the co-precipitation reaction time in the co-precipitation method is between 1 minute and 30 minutes.

[0033] Furthermore, the specific implementation of the co-precipitation method is, for example, to mix the aforementioned materials in solvent water to prepare a 2M metal solution, and stir to suspend the corresponding materials, and then 0.5 Mn 1.5 O4 precursor and dopant are insoluble in solvents (IPA, MEK, methanol, toluene), so a solvent is added in a 1:1 ratio with the above materials to cause precipitation.

[0034] Next, a filtering process is performed to remove the solvent (e.g., water) of the copper-titanium doped lithium nickel manganese oxide precursor, the solid portion is taken out, and a sintering process is performed to complete the lattice rearrangement, and copper and titanium are added to the lattice of nickel manganese oxide to obtain a precursor of lithium nickel manganese oxide doped with copper and titanium. Here, the sintering process can be a high-temperature sintering process with a temperature between 400°C and 1000°C, but the present invention is not limited thereto. In addition, the sintering process time can be between 6 hours and 24 hours, and the sintering atmosphere is air or oxygen atmosphere (oxygen is 99.99% pure oxygen, and air is a general atmospheric environment) for calcination.

[0035] It should be noted that by controlling the co-precipitation agent, co-precipitation reaction temperature and co-precipitation reaction time, sintering process temperature, etc., the particle size of the powder precursor can be between 0.5um and 20um. In addition, by doping lithium nickel manganese oxide powder with copper and titanium, the inactive elements of titanium's electronic configuration and manganese metal ions (Mn 4+ 、Ti 4+), effectively providing structural stability during cycling, while nickel metal ions (Ni 2+ ) and copper metal ions (Cu 2+ ) ions effectively provide high-potential capacitance during the cycle process. Therefore, the copper-titanium doping introduced in the present invention can further enhance the performance of the lithium battery in terms of structure and capacitance.

[0036] The precursor of lithium nickel manganese oxide doped with copper and titanium is mixed with a carbon source, and a nitrogen source is coated by a supercritical fluid method to obtain lithium nickel manganese oxide doped with copper, titanium, nitrogen and carbon.

[0037] First, a carbon source and a precursor of lithium nickel manganese oxide doped with copper and titanium are dry-mixed by a three-dimensional mixer (model POETWQ M10) and then secondary calcined in a tubular furnace to expose the carbon source on the surface of the lithium nickel manganese oxide to improve the gram capacity efficiency of the powder. Here, the carbon source includes graphene, glucose or a combination thereof.

[0038] Next, a nitrogen source is coated by a supercritical fluid method to modify the copper- and titanium-doped lithium nickel manganese oxide disclosed on the surface of the carbon material. For example, a nitrogen source is coated by a supercritical fluid method, and the precursors of dopamine and copper- and titanium-doped lithium nickel manganese oxide are added to a high-pressure reactor, and the reaction temperature is 100°C to 40°C. The pressure is increased to 100 to 50 atm by carbon dioxide, and the reaction is performed for 8 hours to modify the copper- and titanium-doped lithium nickel manganese oxide disclosed on the surface of the carbon material. A nitrogen-carbon doped layer is formed on the surface of the lithium nickel manganese oxide. In this way, the conductivity and gram capacity of the material can be further improved. In addition, the nitrogen-doped carbon material formed on the surface of the lithium nickel manganese oxide doped with copper and titanium can also increase the surface active sites of the material to reduce the energy barrier encountered when ions penetrate, so it is significantly beneficial for the transfer of lithium ions and improving the effect of cycle testing. Here, the nitrogen source includes dopamine, p-phenylenediamine or a combination thereof.

[0039] Furthermore, since the size of nitrogen is similar to that of carbon, nitrogen can replace part of the carbon and fill the surface of the lithium nickel manganese oxide to further increase the specific capacitance, but the present invention is not limited thereto.

[0040] In addition, nitrogen doping is a modification technology in carbon materials. Its principle is to use nitrogen to replace some carbon atoms in fullerenes, carbon nanotubes, graphene or the like. Since the size of nitrogen atoms is close to that of carbon, the two are highly compatible. Nitrogen can be easily doped into the lattice of carbon materials. In the NC bonds generated after doping, N atoms will attract electrons on adjacent C atoms, inducing them to produce electronic defects, thereby promoting the conduction of electrons in the material. Therefore, doping with nitrogen atoms on the surface of carbon materials can effectively enhance their conductivity and catalytic properties.

[0041] It should be noted that supercritical fluid extraction (SFE) is a technique used to separate and extract compounds, usually using supercritical fluid as an extractant. Supercritical fluid is a state of matter between gas and liquid, with special physical and chemical properties that make it an effective extractant in some cases. For example, under normal conditions, supercritical fluid can be adjusted to a supercritical state by adjusting pressure and temperature, at which time it can have the following characteristics: High diffusivity: The diffusion properties of supercritical fluids are similar to those of liquids, which allows them to effectively penetrate and interact with compounds in solid samples, allowing liquids and solid samples to be mixed evenly; Adjustability: By adjusting pressure and temperature, the density and solubility of supercritical fluids can be controlled, thereby adjusting the selectivity and efficiency of the extraction process; Low surface tension: Supercritical fluids have lower surface tension than liquids, which helps to better penetrate solid samples; Reversibility: Supercritical fluids can quickly change states when changing pressure and temperature, which allows the extracted compounds to be easily separated from the supercritical fluid. Supercritical fluid methods are widely used in different fields, including food, medicine, cosmetics, environmental analysis, etc. It can be used to extract natural products, remove impurities, separate compounds, and other applications because the supercritical fluid extraction process does not require the use of organic solvents, thereby reducing environmental impact and the possibility of residues.

[0042] The copper-titanium-nitrogen-carbon-doped lithium nickel manganese oxide of the present invention is described in detail below by way of examples. However, the following examples are not intended to limit the present invention. Here, other undescribed compositions and specifications of the lithium battery should be obtained by a person of ordinary skill in the art according to any content included in the spirit and scope of the attached patent application.

[0043] Positive electrode material of Example 1 (lithium nickel manganese oxide doped with copper and titanium modified by nitrogen-doped carbon material)

[0044] 41.83 g (0.168 mol) of nickel acetate (Ni(CH3COO)2 4H2O) and 10.38 g (0.06 mol) of manganese acetate (Mn(CH3COO)2) were dissolved in 228 ml of ethylenediamine at a molar ratio of 1:2.8, and the total concentration of metal ions was 1.0 M; 27.5 g (0.458 mol) of urea was added at a molar ratio of urea to metal ions of 2:1, and magnetic stirring was performed for 30 minutes. After magnetic stirring for 2 hours, the mixed solution was transferred to a high-pressure reactor, sealed and reacted at 80°C to 170°C for 10 hours, cooled naturally to room temperature, and the obtained precipitate was centrifuged (in a centrifuge with a rotation speed of 10000RPM), the supernatant was removed and washed, and the solution was alkaline; the precipitate was washed with water and placed in a 120°C oven for drying. After drying, Ni 0.25 Mn 0.75 CO3 precursor.

[0045] Next, the obtained Ni 0.25 Mn 0.75 The CO3 precursor was pre-calcined at 400°C to 700°C for 3 hours, then mechanically mixed with LiOH·H2O at a molar ratio of Li:(Ni+Mn)=1.05:2, calcined in air at 800°C for 12 hours, and then sintered at 800°C to 1000°C for 10 hours. After natural cooling and grinding, LiNi 0.5 Mn 1.5 O4 positive electrode material.

[0046] Then, copper acetate (7.2 g) and titanium nitrate (8.4 g) were added to the lithium nickel manganese oxide powder and mixed with a three-dimensional mixer to achieve uniform mixing. The above materials were then mixed in a solvent (water) to form a 2M metal solution, and stirred to suspend the corresponding materials. 0.5 Mn 1.5 Due to the characteristics of O4 precursor and dopant being insoluble in solvents (IPA, MEK, methanol, toluene), a solvent is added in a 1:1 ratio with the above-mentioned materials to make them precipitate, wherein the co-precipitation reaction temperature in the co-precipitation method is between room temperature and 100°C, and the co-precipitation reaction time in the co-precipitation method is 30 minutes.

[0047] Next, a filtration process is performed to remove the solvent (e.g., water) of the copper-titanium doped lithium nickel manganese oxide precursor, and the solid portion is taken out, and a sintering process is performed to complete the lattice rearrangement, and copper and titanium are added to the nickel manganese oxide lattice to obtain a precursor of lithium nickel manganese oxide doped with copper and titanium. Here, the sintering temperature is between 400° C. and 1000° C. and the sintering time is 10 hours.

[0048] Then, the obtained product is mixed with a water-soluble carbon-containing organic compound in a ratio of 100:10-20, and calcined at 600°C for 2 to 3 hours under the protection of an inert gas to obtain carbon-coated lithium nickel manganese oxide. Then, a nitrogen source is coated by a supercritical fluid method, and precursors of dopamine and lithium nickel manganese oxide are added to a high-pressure reactor. The reaction temperature is 100°C to 40°C, the pressure is 100atm to 50atm, and the reaction is carried out for 8 hours to modify the copper- and titanium-doped lithium nickel manganese oxide with carbon material disclosed on the surface of the nitrogen-doped lithium nickel manganese oxide, and a nitrogen-carbon doped layer is formed on the surface of the lithium nickel manganese oxide.

[0049] Positive electrode material of comparative example 1 (lithium nickel manganese oxide material)

[0050] 41.83 g (0.168 mol) of nickel acetate (Ni(CH3COO)2·4H2O) and 10.38 g (0.06 mol) of manganese acetate (Mn(CH3COO)2) were dissolved in 228 ml of ethylenediamine according to the molar ratio of the elements of 1:2.8, and the total concentration of metal ions was 1.0 M; 27.5 g (0.458 mol) of urea was added according to the molar ratio of urea to metal ions of 2:1, and mixed in a three-dimensional mixer for 30 minutes, and then the mixed solution was magnetically stirred for 2 hours and then transferred to a high-pressure reactor, sealed and reacted at 80 to 170°C for 10 hours, cooled naturally to room temperature, and the obtained precipitate was centrifuged (in a centrifuge with a rotation speed of 10000RPM), the supernatant was removed and washed, and the solution was alkaline; the precipitate was washed with water and placed in a 120°C oven for drying. After drying, Ni 0.25 Mn 0.75 CO3 precursor.

[0051] The obtained Ni 0.25 Mn 0.75 The CO3 precursor is first pre-calcined at 400°C to 700°C for 3 hours, then mixed with LiOH·H2O in a three-dimensional mixer at a molar ratio of Li:(Ni+Mn)=1.05:2, calcined at 800°C in air for 12 hours, and then sintered at 800°C to 1000°C for 10 hours, and then naturally cooled and ground to obtain the LiNi 0.5 Mn 1.5 O4 positive electrode material.

[0052] Positive electrode material of Comparative Example 2 (lithium nickel manganese oxide doped with copper and titanium)

[0053] 41.83 g (0.168 mol) of nickel acetate (Ni(CH3COO)2·4H2O) and 10.38 g (0.06 mol) of manganese acetate (Mn(CH3COO)2) were dissolved in 228 ml of ethylenediamine at a molar ratio of 1:2.8, and the total concentration of metal ions was 1.0 M; 27.5 g (0.458 mol) of urea was added at a molar ratio of urea to metal ions of 2:1, and the mixed solution was magnetically stirred for 2 hours, transferred to a high-pressure reactor, sealed and reacted at 80°C to 170°C for 10 hours, cooled naturally to room temperature, and the resulting precipitate was centrifuged (in a centrifuge with a rotation speed of 10000RPM), the supernatant was removed and washed, and the solution was alkaline; the precipitate was washed with water and placed in an oven at 120°C for drying, and after drying, Ni 0.25 Mn 0.75 CO3 precursor.

[0054] The obtained Ni 0.25 Mn 0.75 The CO3 precursor is first pre-calcined at 400-700°C for 3 hours, then mechanically mixed with LiOH·H2O at a molar ratio of Li:(Ni+Mn)=1.05:2, calcined in air at 800°C for 12 hours, and then sintered at 800°C to 1000°C for 10 hours, and then naturally cooled and ground to obtain the LiNi 0.5 Mn 1.5 O4 positive electrode material.

[0055] Copper acetate (7.2 g) and titanium nitrate (8.4 g) were added to the above-mentioned lithium nickel manganese oxide powder and mixed with a three-dimensional mixer to achieve the purpose of mixing uniformly. The above-mentioned materials were then mixed in solvent water to prepare a 2M metal solution, and stirred to suspend the corresponding materials. 0.5 Mn 1.5 Due to the characteristics of O4 precursor and dopant being insoluble in solvents (IPA, MEK, methanol, toluene), a solvent is added in a 1:1 ratio with the above-mentioned materials to make them precipitate, wherein the co-precipitation reaction temperature in the co-precipitation method is between room temperature and 100°C, and the co-precipitation reaction time in the co-precipitation method is 30 minutes.

[0056] Next, a filtration process is performed to remove the solvent (e.g., water) of the copper-titanium doped lithium nickel manganese oxide precursor, and the solid portion is taken out, and a sintering process is performed to complete the lattice rearrangement, and copper and titanium are added to the nickel manganese oxide lattice to obtain a precursor of lithium nickel manganese oxide doped with copper and titanium. Here, the sintering temperature is between 400° C. and 1000° C. and the sintering time is 10 hours.

[0057] Positive electrode material of Comparative Example 3 (lithium nickel manganese oxide material modified by carbon doping)

[0058] 41.83 g (0.168 mol) of nickel acetate (Ni(CH3COO)2·4H2O) and 10.38 g (0.06 mol) of manganese acetate (Mn(CH3COO)2) were dissolved in 228 ml of ethylenediamine at a molar ratio of 1:2.8, and the total concentration of metal ions was 1.0 M; 27.5 g (0.458 mol) of urea was added at a molar ratio of urea to metal ions of 2:1, and the mixed solution was magnetically stirred for 2 hours, transferred to a high-pressure reactor, sealed, reacted at 80°C to 170°C for 10 hours, cooled naturally to room temperature, and the resulting precipitate was centrifuged (in a centrifuge with a rotation speed of 10000RPM), the supernatant was removed and washed, and the solution was alkaline; the precipitate was washed with water and placed in an oven at 120°C for drying, and after drying, Ni 0.25 Mn 0.75 CO3 precursor.

[0059] The obtained Ni 0.25 Mn 0.75 The CO3 precursor is first pre-calcined at 400°C to 700°C for 3 hours, then mechanically mixed with LiOH·H2O at a molar ratio of Li:(Ni+Mn)=1.05:2, calcined at 800°C in air for 12 hours, and then sintered at 800°C to 1000°C for 10 hours, and then naturally cooled and ground to obtain the LiNi 0.5 Mn 1.5 O4 positive electrode material.

[0060] Copper acetate (7.2 g) and titanium nitrate (8.4 g) were added to the above-mentioned lithium nickel manganese oxide powder and mixed with a three-dimensional mixer to achieve the purpose of mixing uniformly. The above-mentioned materials were mixed in solvent water to prepare a 2M metal solution, and stirred to suspend the corresponding materials. 0.5 Mn 1.5 Due to the characteristics of O4 precursor and dopant being insoluble in solvents (IPA, MEK, methanol, toluene), a solvent is added in a 1:1 ratio with the above-mentioned materials to make them precipitate, wherein the co-precipitation reaction temperature in the co-precipitation method is between room temperature and 100°C, and the co-precipitation reaction time in the co-precipitation method is 30 minutes.

[0061] Next, a filtering process is performed to remove the solvent (such as water) of the copper-titanium doped lithium nickel manganese oxide precursor, take out the solid part, and perform a sintering process to complete the lattice rearrangement, add copper and titanium to the nickel manganese oxide lattice to obtain a precursor of lithium nickel manganese oxide doped with copper and titanium. Here, the sintering temperature is between 400°C and 1000°C and the sintering time is 10 hours, and then the above-obtained product is mixed with a water-soluble carbon-containing organic compound at a weight ratio of 100:1 to 20 (7 to 12 is the best), and calcined at 600°C for 2 to 3 hours under inert gas protection to obtain carbon-coated lithium nickel manganese oxide.

[0062] Positive electrode material of Comparative Example 4 (lithium nickel manganese oxide material modified by nitrogen-doped carbon material)

[0063] 41.83 g (0.168 mol) of nickel acetate (Ni(CH3COO)2·4H2O) and 10.38 g (0.06 mol) of manganese acetate (Mn(CH3COO)2) were dissolved in 228 ml of ethylenediamine at a molar ratio of 1:2.8, and the total concentration of metal ions was 1.0 M; 27.5 g (0.458 mol) of urea was added at a molar ratio of urea to metal ions of 2:1, and the mixed solution was magnetically stirred for 2 hours, transferred to a high-pressure reactor, sealed and reacted at 80-170°C for 10 hours, cooled naturally to room temperature, and the obtained precipitate was centrifuged (centrifuged in a centrifuge with a rotation speed of 10000RPM), the supernatant was removed and washed, and the solution was alkaline; the precipitate was washed with water and placed in a 120°C oven for drying, and after drying, Ni 0.25 Mn 0.75 CO3 precursor.

[0064] The obtained Ni 0.25 Mn 0.75 The CO3 precursor is first pre-calcined at 400°C to 700°C for 3 hours, then mechanically mixed with LiOH·H2O at a molar ratio of Li:(Ni+Mn)=1.05:2, calcined at 800°C in air for 12 hours, and then sintered at 800°C to 1000°C for 10 hours, and then naturally cooled and ground to obtain the LiNi 0.5 Mn 1.5 O4 positive electrode material.

[0065] The product obtained above is mixed with a water-soluble carbon-containing organic compound in a weight ratio of 100:10-20, and calcined at 600°C for 2-3 hours under the protection of an inert gas to obtain carbon-coated lithium nickel manganese oxide. Next, a nitrogen source is coated by a supercritical fluid method, and dopamine and a precursor of lithium nickel manganese oxide are added to a high-pressure reactor, the reaction temperature is 100-40°C, and carbon dioxide is introduced to adjust the pressure to 100-50atm, and the reaction is performed for 8 hours to modify the lithium nickel manganese oxide with carbon material on the surface of the above-mentioned lithium nickel manganese oxide by nitrogen doping, and a nitrogen-carbon doping layer is formed on the surface of the above-mentioned lithium nickel manganese oxide.

[0066] Preparation of lithium batteries

[0067] First, the positive electrode material and conductive carbon black (Super P) of the embodiment are placed in a 120°C oven for 1 hour to remove moisture. Next, 80 parts by weight of the positive electrode material of the embodiment, 10 parts by weight of conductive carbon black (Super P) and 10 parts by weight of adhesive (PVDF (HSV-900)) are weighed and mixed in a solvent (NMP) to form a uniform positive electrode slurry. Then, the positive electrode slurry is coated on aluminum foil with a scraper, with a wet film thickness of 200 μm and a coating speed of 2 mm / s, and then moved to an oven to dry at 60-120°C, followed by calendering, with a calendering thickness of 0.038 mm, and the rolled positive electrode sheet is cut into a circular sheet with a diameter of 13 mm.

[0068] After that, prepare the CR2032 button battery pack. First, place the negative electrode (metal lithium sheet) lower cover flat on an insulating platform, place the metal lithium sheet with a diameter of 15.8 mm in the center of the negative electrode lower cover, and use a tablet press to flatten the lithium sheet. Then drop an appropriate amount of liquid electrolyte (1M LiPF6 in EC:DEC 1:1v / v%) on a commercially available separator with a diameter of 18 mm (trade name: Celgard 2400), and then place the separator on top of the lithium sheet, followed by the positive electrode, spacer, reed, and positive electrode cover prepared according to the above method. Next, use insulating tweezers to place the button-type lithium battery into the battery press with the negative electrode facing up, and press with a pressure of 800 Pa to complete the battery assembly.

[0069] Comparative Example

[0070] A button-type lithium battery was prepared in the same manner as in the example, except that the positive electrode material of the comparative example prepared as above was used instead of the positive electrode material of the example.

[0071] Electrochemical characteristics analysis:

[0072] Initial discharge capacity and capacity decay rate

[0073] The button-type lithium batteries of Example 1 and Comparative Examples 1-4 were discharged at 0.5C at 25°C and the gram capacity results are shown in Table 1. The charge and discharge capacity calculation formula of different positive electrode materials is as follows: gram capacity (mAh / g) = (current (mA) × time (h)) / (mass of active material (g)).

[0074] Table 1

[0075]

[0076] In summary, the present invention improves the energy density of lithium nickel manganese oxide materials by copper-titanium-nitrogen-carbon doping technology to solve the problem of low gram capacity. Therefore, the lithium battery positive electrode material of the present invention can effectively increase the gram capacity and thus reduce the cost.

[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A positive electrode material for a lithium battery, characterized in that: Including copper-titanium-nitrogen-carbon doped lithium nickel manganese oxide.

2. The positive electrode material for lithium battery according to claim 1, characterized in that: The weight ratio of lithium nickel manganese oxide: copper / titanium: nitrogen / carbon in the copper-titanium-nitrogen-carbon doped lithium nickel manganese oxide is between 1:0.4:0.1 and 1:0.1:0.

1.

3. The positive electrode material for lithium battery according to claim 1, characterized in that: The average particle size of the copper-titanium-nitrogen-carbon doped lithium nickel manganese oxide is between 0.5 microns and 20 microns.

4. A method for manufacturing a positive electrode material for a lithium battery, characterized in that: include: Performing a co-precipitation method, a filtering process and a sintering process to prepare a precursor of lithium nickel manganese oxide doped with copper and titanium from a copper source, a titanium source and lithium nickel manganese oxide powder; as well as The precursor of the lithium nickel manganese oxide doped with copper and titanium is mixed with a carbon source, and a nitrogen source is coated by a supercritical fluid method to obtain lithium nickel manganese oxide doped with copper, titanium, nitrogen and carbon.

5. The method for producing a positive electrode material for a lithium battery according to claim 4, characterized in that: The copper source includes copper chloride, copper sulfate, copper sulfite, copper nitrate, copper acetate or a combination thereof.

6. The method for producing a positive electrode material for a lithium battery according to claim 4, characterized in that: The titanium source includes titanium chloride, titanium sulfate, titanium nitrate or a combination thereof.

7. The method for producing a positive electrode material for a lithium battery according to claim 4, characterized in that: The nitrogen source includes dopamine, p-phenylenediamine or a combination thereof.

8. The method for producing a positive electrode material for a lithium battery according to claim 4, characterized in that: The carbon source includes graphene, glucose or a combination thereof.

9. The method for producing a lithium battery positive electrode material according to claim 4, characterized in that: The coprecipitation agent used in the coprecipitation method includes water, ethanol, isopropanol, acetone, methyl ethyl ketone, ammonia water, sodium hydroxide, sodium carbonate or a combination thereof; the coprecipitation reaction temperature in the coprecipitation method is between 25°C and 100°C, and the coprecipitation reaction time in the coprecipitation method is between 1 minute and 30 minutes.

10. The method for producing a positive electrode material for a lithium battery according to claim 4, characterized in that: The temperature of the sintering process is between 400°C and 1000°C.